If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + -3) = 5(y + -1) Reorder the terms: 4(-3 + y) = 5(y + -1) (-3 * 4 + y * 4) = 5(y + -1) (-12 + 4y) = 5(y + -1) Reorder the terms: -12 + 4y = 5(-1 + y) -12 + 4y = (-1 * 5 + y * 5) -12 + 4y = (-5 + 5y) Solving -12 + 4y = -5 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -12 + 4y + -5y = -5 + 5y + -5y Combine like terms: 4y + -5y = -1y -12 + -1y = -5 + 5y + -5y Combine like terms: 5y + -5y = 0 -12 + -1y = -5 + 0 -12 + -1y = -5 Add '12' to each side of the equation. -12 + 12 + -1y = -5 + 12 Combine like terms: -12 + 12 = 0 0 + -1y = -5 + 12 -1y = -5 + 12 Combine like terms: -5 + 12 = 7 -1y = 7 Divide each side by '-1'. y = -7 Simplifying y = -7
| 1.5d+3.25=1+2.25 | | 4x-7=7x-7 | | 7.32x-9.10=2.75x-18.23 | | 3np=r | | 3(2x-3)=-2x-1 | | 6x+10=2(x-1) | | r=3np | | y=-x-10x-21 | | 3y+44=94 | | 6(-3r+2)=66 | | 1.8x-5=-2.7x+37 | | 5x-62=-28 | | 45.2x+3.78=4.2x | | 2(w/3+1/4)=4+w/3 | | 4x+5-27=180 | | 39/5f-7/30f=5/6 | | (1/5)*((5x^2)-2x) | | -4x+2=-7x+38 | | z/3=3z-4/5 | | 4/5+2=6 | | 1a+1b=1c | | ln(x)/7 | | 9x^2-613=0 | | 1a+1b=2c | | 3.2x+4.6=32.7 | | -8b+6=9 | | 7=5x+3(x-2)+5 | | 6=7-2n+5 | | 7t-3s(2+t)s= | | x/2+7=.75x-4 | | 3y+8y= | | (x^2)/(5x^2) |